The role of investment attractiveness in the development of higher education in Uzbekistan - Jonuzokov, Kulmamatovich , Mirzabek (THE INNOVATION ECONOMY, 2024)
This article examines the critical role of investment in higher education in promoting rapid economic development in Uzbekistan. It emphasized the attractiveness of investments in higher education in combination with the national strategy “Uzbekistan - 2030”. The article presents the concepts of “investment” and “investment attractiveness” based on existing literature and expert opinions. In conclusion, proposals for developing the investment attractiveness of higher education services are presented. Also, the nature of investments is clearly indicated in Article 2 of the Law of the Republic of Uzbekistan “On Investment Activities”, according to which “Investments consist of tangible and intangible benefits and rights associated with economic and other objects of activity.” Based on the above, in our opinion, it is necessary to take into account the need and attractiveness of industries and industries when explaining the nature of investments. Therefore, investments consist of the value of funds (capital flows) directed to various sectors and branches of the national economy of our country with the aim of making a profit. Investments in higher education are the cost of funds (public and private capital) allocated for the development of higher education services in the field of education of the national economy of the republic.